Manejo da cultura da soja e plantas invasoras sob cobertura vegetal de aveia preta e consórcio de aveia preta, ervilhaca comum e nabo forrageiro - Mauli, Marcia Maria (2009)
The adjustment of a cover crop to the agricultural system, with species whose chemical composition has substances able to control weeds, is a promising alternative to decrease herbicides application in agriculture. So, this trial aimed at analyzing the interference of black oats residues as well as black oat, common vetch and forage turnip consortium on weeds incidence, seeds emergence, seedling emergence, plants development, soybean productivity and its harvested seeds quality. The trial was carried out on field, from 2007 to 2008, with 5 m x 2 m plots and 1 m of border among them, distributed in seven randomized treatments with five replications each. During the crop development, the following parameters were evaluated: emergence speed index, plants development and weeds incidence. After harvest, in the laboratory, harvested seeds were evaluated according to: water content determination, weight of 100 seeds, purity, productivity, percentages of germination and vigor. It was a factorial experimental design with two factors plus one control and the averages were compared by the Tukey test at 5% level of significance. The weeds species did not differ statistically among the treatments. By and large, the treatments did not influence on plants heights, but increased the soybean productivity. However, the seeds showed less vigor when under the accelerated aging test. The seeds purity was inferior when they were under black oats crop. The weight of 100 seeds was changed by the treatments and they were heavier when grown on black oats. The other analyzed parameters did not show any statistic difference. It is, therefore, concluded that these species are good alternatives as winter covers in soybean crop under rotation system, since they improve the agronomic aspects of this culture.